Digital Fingerprints: Business Ethics in the Use of Geolocation for Employee Monitoring - García Lizárraga, Dwight Guillermo (2024)
The use of geolocation technology to monitor employees poses an ethical challenge in balancing legitimate business interests with the protection of workers' fundamental rights, such as privacy and personal data protection. It is important that geolocation devices are installed on company-owned vehicles or equipment, limiting their use to working hours and obtaining prior consent from employees on their purpose and scope. Data collected through geolocation must be treated with respect for the principles of legality, proportionality, necessity and transparency, and guaranteeing the employees' right of defense. Companies that use or plan to use geolocation devices must do so in an ethical manner, respecting the rights of employees and complying with current legal and social regulations, fostering an environment of dialogue and participation in the organization.